THEMATIC PROGRESSION PATTERN IN SHORT STORY "THE LAST LEAF" BY O. HENRY - Witri Karunia Gea (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2024)
Discourse analysis is a method for studying written or spoken language. This research aimed at findings the patterns of thematic progression contained in the short story “The Last Leaf” by O. Henry. The method used in this research was qualitative method. The source of the data in this research was the text of short story “The last Leaf” by O. Henry and selected 29 part of the text. The result of the data analysis show that all the patterns of thematic progression were used in the short story “The last Leaf” by O.Henry. There were found 19 the constant Theme pattern, 10 the linier Theme pattern, 6 the split Rheme pattern and 4 Derived Themes. Totals were 39 patterns. It is show that short story "The Last Leaf" by O. Henry used all the patterns of thematic progression but to organize this short story the writer has combined the pattern for some the parts in the short story "The Last Leaf" by O. Henry. The dominant pattern used was constant Theme Pattern. Therefore, it is concluded that thematic progression pattern is very important to develop the sentence the text. It is suggested to the readers to use the result of this research as references to enrich their vocabulary, knowledge, especially in thematic progression as way to develop ideas in the paragraph and take benefits of this research.